2020
DOI: 10.3168/jds.2019-17062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage type in the ovine diet on the nutritional profile of sheep milk cheese fat

Abstract: The high nutritional value of sheep milk can be advantageous in the manufacture of cheese, and fat plays an important role in sheep cheese properties. The aim of this study was to investigate the effect of feeding common hay or silage diets used in commercial farms on the nutritional value of sheep cheese fat. We also monitored the effect of cheese ripening period on the fatty acid profile. Cheeses were produced from milk of sheep fed hay and silage diets from 8 farms, on 4 separate occasions (February, May, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
3
13
0
1
Order By: Relevance
“…The result for SFA, which had no significant variations, is consistent with results of Renes et al [74]. The higher values of CLA and vaccenic acid found in hay vs. silage in the present research is confirmed by Segato et al [73], although these authors consider maize silage instead of hay silage.…”
Section: Comparison Between Cheeses Produced In Winter Seasonsupporting
confidence: 93%
See 2 more Smart Citations
“…The result for SFA, which had no significant variations, is consistent with results of Renes et al [74]. The higher values of CLA and vaccenic acid found in hay vs. silage in the present research is confirmed by Segato et al [73], although these authors consider maize silage instead of hay silage.…”
Section: Comparison Between Cheeses Produced In Winter Seasonsupporting
confidence: 93%
“…The result that PUFA are higher in hay silage (haylage) than in hay is consistent with the study of Schingoethe et al [75] that found the same result, explaining it as a trend toward increased unsaturation for feeding fermented forages [75]. On the contrary, other authors [74] found higher values of PUFA in the hay group than in the silage group, but the silage is not the same (in this case it is vetch silage, and the research is on sheep milk and cheese).…”
Section: Comparison Between Cheeses Produced In Winter Seasonsupporting
confidence: 90%
See 1 more Smart Citation
“…It is a fact that the increasing attention of consumers to the nutritional and health aspects of food has created a tendency among sheep farmers and dairies to produce milk and dairy products, respectively, with a modified lipid composition. The fat concentration in milk can be altered by diet, especially by factors affecting rumen fermentation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cheese has a great importance in the economy of sheep's milk-producing regions. Sheep's milk possesses a high nutritional, important medicinal and therapeutic value, and it can be advantageous in the manufacture of cheese (Renes et al, 2020). In fact, higher protein levels in sheep milk allow the production of cheese with dense matrices, which may confer nutrients essential for microbial survival during fermentation (Balthazar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%